Effect of rolling conditions on the structure and shape memory properties of Fe–Mn–Si alloys - Druker, Ana Velia (2010)
Lattice defects play an important role in controlling the g®e martensitic transformation in shape memory ferrous alloys. This work focuses on the relation between various rolling and annealing processes, the microstructure resulting from the processes, and strain recovery of two Fe-Mn-Si alloys with different stacking fault energies (SFEs). Rolling experiments, conducted over a temperature range from 20ºC to 1000ºC, produce quite different microstructures, which vary from a high dislocation density to a structure containing only few isolated dislocations. In addition, annealing temperature has a very important influence not only on the dislocation arrays but also on the stacking faults remaining in the austenite, whose density depends on the SFE value for the alloy. Within the framework of the processing parameters selected for this work, i.e. roll speed, rolling reductions, processing temperatures and schedules, rolling at intermediate temperatures and annealing at a temperature of 650ºC seem to be the most appropriate method to obtain a microstructure favorable for a nearly full degree of shape recovery.